SOIL ORGANIC CARBON POTENTIAL OF BOZHURISHTE MUNICIPALITY: A CASE STUDY FROM WESTERN BULGARIA - Borislav GRIGOROV (European Journal of Geography)
The current study focuses on the soil organic carbon contents in topsoil (0-30 cm) in Bozhurishte Municipality. The municipality is a part of Sofia Province and it represents a major section of the “Sofia-Bozhurishte Economic Zone”. The aim of the investigation is to reveal how soil organic carbon storages may change in the forthcoming 20 years during a medium and a high scenario. The results of the study display several major zones of a large soil organic carbon pool, located to the northeast and the central parts of the municipality. The section, containing the largest soil organic carbon pool, may experience an increase of 376 400 tons/ha for 20 years in the medium scenario and 499 100 tons/ha in the high scenario. The author concludes that promising results may be used as a basis for an expansion of the study in the neighboring municipalities.